PENGARUH GOOD CORPORATE GOVERNANCE, KOMPOSISI ASSET TETAP, KESEMPATAN TUMBUH DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Yustinus Adhi Setiawan, 13.05.62.0012; Kartika, Andi (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of good corporate governance, asset mix, the chance to grow and the size of the company to the companys performance in the companys corporate governance program preception CGPI index listed on the Indonesia Stock Exchange in 2011-2014. The population used in this study is a company that follows the corporate governance program preception CGPI index listed on the Indonesia Stock Exchange in 2011-2014. The sample in this study were 60 observation data. The sampling technique used purposive sampling. The criteria for the sample in this study is the companies included in the